Neural growth patterns: how random and aligned fibers guide 3D cell organization and pseudospheroid formation - Hlinkova, Jana; Dziemidowicz, Karolina; Ullrich, Mathilde M.; Agger, Anne Eriksson; Lian, Aina-Mari; Reseland, Janne Elin; Samara, Athina (Frontiers in Bioengineering and Biotechnology, 2025)
Background and purposeElectrospun biomaterials replicate the structural complexity of the extracellular matrix (ECM), providing mechanical support and promoting neural cell survival and organization. Fiber orientation is a key determinant of neural cell behavior, influencing adhesion, migration, and differentiation. This study investigates how high seeding density combined with fiber directionality shapes SH-SY5Y culture morphology, gene expression, and early network formation; all critical factors for the design of next-generation scaffolds for neural tissue engineering.MethodsPolycaprolactone (PCL) scaffolds with either random or aligned fiber orientation were fabricated via monoaxial electrospinning. Human SH-SY5Y neuroblastoma cells were seeded at high density and cultured for 7 days, and cell viability was assessed by lactate dehydrogenase (LDH) activity. Neural, ECM, and differentiation markers were analyzed using quantitative PCR, Luminex cytokine profiling, and confocal immunofluorescence.ResultsHydrophobic PCL fibers supported cell adhesion, migration, and proliferation when cells were seeded in small clusters. After 7 days, cell coverage of the fiber-mat was significantly higher on random fibers compared to aligned ones (27.7% vs. 15.8%). Fiber orientation influenced both culture morphology and gene expression. Pseudospheroids formed on both substrates, that differed in perimeter (348.5 µm on random vs. 450.5 µm on aligned fibers, p < 0.05), with no significant difference in thickness (38.4 ± 7.7 µm vs. 43.2 ± 5.5 µm). mRNA expression of connexin 43 and β3-tubulin increased significantly from day 1 to day 7 on random fibers. On aligned fibers, mRNA patterns resembled cells cultured on glass (control), with elevated connexin 31 and doublecortin over time. Immunofluorescence showed early enrichment of nestin on aligned fibers (day 1), and greater expression of β3-tubulin, acetylated tubulin, and connexin 31 on aligned substrates, whereas fibronectin 1 was more prominent on random fibers.ConclusionFiber orientation significantly affected SH-SY5Y cell behaviour, including adhesion, formation of pseudospheroids, and differentiation marker expression under high-density conditions. Random and aligned fibers elicited distinct structural patterns and molecular responses, highlighting the importance of scaffold architecture in the rational design of neuroregenerative platforms. To our knowledge, this is the first study to describe scaffold-anchored neural pseudospheroids as a distinct model from conventional suspension spheroids.